1990
DOI: 10.1203/00006450-199003000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Subcellular Localization of Peroxisomal 3-Ketoacyl-CoA Thiolase in the Zellweger Syndrome and Rhizomelic Chondrodysplasia Punctata

Abstract: ABSTRACT. Fibroblasts from patients with the inherited disorder Zellweger syndrome have few or no peroxisomes; multiple biochemical processes that normally occur in this organelle are defective. Rhizomelic chondrodysplasia punctata (RCDP) is another inherited disorder in which two unrelated peroxisomal metabolic processes, plasmalogen synthesis and phytanic acid oxidation, are impaired despite the normal appearance of peroxisomal structure. It was previously reported that one of the enzymes of peroxisomal fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
2

Year Published

1991
1991
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 45 publications
4
41
2
Order By: Relevance
“…Our results, consistent with those of previous studies (40,43), suggest that the processing of the enzyme precursor is defective in Zellweger syndrome. Our results further suggest that in Zellweger syndrome peroxisomelike elements containing the 22-kD PMP and a 44-kD precursor protein of the P-oxidation enzyme thiolase are formed.…”
Section: Gradient Fractionssupporting
confidence: 83%
See 1 more Smart Citation
“…Our results, consistent with those of previous studies (40,43), suggest that the processing of the enzyme precursor is defective in Zellweger syndrome. Our results further suggest that in Zellweger syndrome peroxisomelike elements containing the 22-kD PMP and a 44-kD precursor protein of the P-oxidation enzyme thiolase are formed.…”
Section: Gradient Fractionssupporting
confidence: 83%
“…The 22-kD PMP associated membrane fraction and a peroxisomal thiolase precursor protein were consistently localized in the same low-density subcellular fractions, as already suspected by Balfe et al (40). These results argue against a general import failure of peroxisomal matrix proteins as the primary defect in Zellweger syndrome.…”
Section: Gradient Fractionssupporting
confidence: 56%
“…Although we did not perform immunocytochemistry to characterize these particles, we can assume that they are different from the peroxisomal particles described in other disorders of peroxisome biogenesis. They had higher density (1.137 g/cm3) than the membrane ghosts observed in Zellweger syndrome (I. I0 g/cm3) (1 6, 17), and RCDP (I. I -1.12 g/cm3) (13,15), and than w-particles (1.13 g/cm3) (18). Another difference is that membrane ghost structures and wparticles in Zellweger syndrome or RCDP do not contain enzyme activities for DHAP-AT and oxidation of VLCFA (15,18), whereas the peroxisome-like structures seen in our patient had significant activity for these enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…RCDP differs from these disorders because peroxisomes are grossly normal in this disease and contain catalase. Moreover, only three peroxisomal functions are impaired (plasmalogen synthesis, oxidation of phytanic acid, and processing of @-ketothiolase) (1 [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 99%
“…More recently, we reported that a peroxisomal matrix enzyme, 3-ketoacyl-CoA thiolase (E.C. 2.3.1.16), could also be found associated with low-density membranous particles, at least in some Zellweger syndrome and rhizomelic chondrodysplasia punctata fibroblast lines, but in a larger molecular weight "unprocessed" form (7).…”
mentioning
confidence: 99%